Analisis Segmentasi Pasar dan Potensi Permintaan Usaha Kuliner: Studi Kasus Best.Camp di Kawasan Megamas, Kota Manado - Yosua Oleh; Cysca Adelaida Juliana Langi; Efendy Rasjid (Journal of Management and Social Sciences, 2026)
This study aims to analyze the market segmentation and demand potential of Best.Camp, a beachfront café operating in the Megamas Area, Manado City. A descriptive qualitative method with a case study approach was employed, using primary data from field observations and secondary data from the Central Bureau of Statistics and the Manado City Population and Civil Registration Office. Market segmentation was analyzed based on geographic, demographic, psychographic, and behavioral aspects, referring to Kotler's segmentation theory. The results show that although the productive age group (15–35 years) accounts for only 33–35% of Manado City's total population, this group dominates up to 55% of the estimated 30,000 daily visitors to the Megamas Area, equivalent to approximately 16,500 productive-age visitors per day. Based on actual field data, Best.Camp's current sales reach 30 portions per day for Ayam Crispi Sambal Mata and 35 cups per day for Best Coffee Milk, with market shares of 23.64% and 17.40%, respectively, relative to total market demand for similar products in the area. The substantial untapped market potential indicates significant room for growth, suggesting that Best.Camp can further expand its production capacity and marketing strategy to capture a larger share of the Megamas culinary market.